EVALUATION OF LEADERSHIP AND MANAGEMENT PROGRAMS FOR TEACHER PROFESSIONAL DEVELOPMENT - Erwin Erwin; Nira Mellina Pangestika; Mustopa (Indonesian Journal of Education (INJOE), 2024)
This study aims to evaluate the effectiveness of leadership and management programs in the context of teacher professional development, using a literature review approach. The results show that effective leadership and management programs can strengthen teachers' capacity in decision-making, communication, conflict management and problem-solving, further contributing to the creation of a supportive and innovative learning environment. Furthermore, findings indicate that participation in these programs is positively associated with improved student performance, through more effective teaching and more efficient classroom management. Feedback from peers and program participants also highlighted the importance of elements such as mentoring, project-based training and self-reflection in improving the quality of leadership and management in the school environment. Overall, this literature review confirms that investing in teachers' professional leadership and management development is a vital strategy for improving teaching quality and educational outcomes. This research suggests that schools and other educational institutions design and implement structured and sustainable programs for teacher leadership coaching as part of their professional development strategies